2015
DOI: 10.3109/03008207.2015.1016609
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound stimulates matrix metabolism of human annulus fibrosus cells mediated by transforming growth factorβ1 and extracellular signal-regulated kinase pathway

Abstract: The findings suggested that LIPUS could be useful as a physical stimulation of cell metabolism for the repair of the AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…Type 1 diabetes mellitus (T1DM) causes skeletal muscle atrophy [ 2 , 10 , 30 ]. LIPUS can increase the differentiation of muscular lineage cells and favor tissue regeneration [ 13 , 31 , 32 ]. Therefore, we investigated whether LIPUS could improve T1DM-induced skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) causes skeletal muscle atrophy [ 2 , 10 , 30 ]. LIPUS can increase the differentiation of muscular lineage cells and favor tissue regeneration [ 13 , 31 , 32 ]. Therefore, we investigated whether LIPUS could improve T1DM-induced skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed an increase in glucose consumption and the initiation of an energy-consuming activity. Chen et al (2015) [62], instead, proved that LIPUS could effectively stimulate matrix metabolism of a certain cell line through the up-regulation of specific pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al ( 28 ) also illustrated that both Smad2/3 and Smad1/5/8 were upregulated in degenerative bovine NPCs, and activated Smad1/5/8 could inhibit Smad2/3 expression, leading to further IDD. Accumulating evidence has indicated that TGF-β can stimulate ECM production via Smad2/3 overexpression ( 29 , 30 ). TIMP-3 has a specific protective effect on cartilage, and the TGF-β/Smad2/3 pathway can enhance the expression of TIMP-3( 31 ), thereby explaining the protective effect on the ECM.…”
Section: Discussionmentioning
confidence: 99%